2009
DOI: 10.3233/ies-2009-0350
|View full text |Cite
|
Sign up to set email alerts
|

Changes in upper body strength and body composition after 8 weeks indoor climbing in youth

Abstract: The aim of this study was to investigate whether climbing in children leads to the development of upper limb strength and endurance, and changes in body composition. Fifty young climbers aged 10-17 participated in an 8 week climbing program. Metres climbed were used as a factor to assess the effect of climbing. Two groups were ex post formed with a limit of 320 metres climbed. Boys and girls from the group that climbed more metres significantly increased their performance in bent-arm hang time (boys from 35.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 23 publications
(28 reference statements)
3
35
1
1
Order By: Relevance
“…That physical activity of this type has a positive effect on grip strength has been shown in experimental studies with children (Baláš et al, 2009;Lirgg et al, 2011;Siegel et al, 1989) and young women (Thomas et al, 2008). Although there has been no experimental attempt to limit strenuous physical activity involving the upper extremities, it seems reasonable to believe this would result in decreased grip strength.…”
Section: Discussionmentioning
confidence: 95%
“…That physical activity of this type has a positive effect on grip strength has been shown in experimental studies with children (Baláš et al, 2009;Lirgg et al, 2011;Siegel et al, 1989) and young women (Thomas et al, 2008). Although there has been no experimental attempt to limit strenuous physical activity involving the upper extremities, it seems reasonable to believe this would result in decreased grip strength.…”
Section: Discussionmentioning
confidence: 95%
“…Climbing seems be a suitable physical activity for children to develop muscular strength and endurance (Baláš & Bunc, 2007;Baláš et al, 2009). Baláš et al (2009) found that indoor wall climbing with a higher volume of metres climbed can influence Physiological demands of indoor wall climbing in children 187…”
Section: Discussionmentioning
confidence: 98%
“…Baláš et al (2009) found that indoor wall climbing with a higher volume of metres climbed can influence Physiological demands of indoor wall climbing in children 187…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations